Role of small bowel capsule endoscopy in the diagnosis and management of iron deficiency anemia in elderly: A comprehensive review of the current literature - Muhammad, Adnan (Baishideng Publishing Group Inc, 2014)
Iron deficiency anemia (IDA) is common and often under recognized problem in the elderly. It may be the result of multiple factors including a bleeding lesion in the gastrointestinal tract. Twenty percent of elderly patients with IDA have a negative upper and lower endoscopy and two-thirds of these have a lesion in the small bowel (SB). Capsule endoscopy (CE) provides direct visualization of entire SB mucosa, which was not possible before. It is superior to push enteroscopy, enteroclysis and barium radiography for diagnosing clinically significant SB pathology resulting in IDA. Angioectasia is one of the commonest lesions seen on the CE in elderly with IDA. The diagnostic yield of CE for IDA progressively increases with advancing age, and is highest among patients over 85 years of age. Balloon assisted enteroscopy is used to treat the lesions seen on CE. CE has some limitations mainly lack of therapeutic capability, inability to provide precise location of the lesion and false positive results. Overall CE is a very safe and effective procedure for the evaluation of IDA in elderly.